ANALISIS NON PERFORMING FINANCING (NPF) BANK UMUM SYARIAH DI INDONESIA TAHUN 2007 – 2012 - . Solihatun (Jurnal Ekonomi Pembangunan, 2014)
The purpose of this study was to determine the effect of Financing to Deposit Ratio (FDR) and Return on Assets (ROA) as an internal indicator banks representing aspects of profit and liquidity and the inflation rate as an indicator of bank external (macroeconomic) the ratio of financing problems are reflected in the ratio Non-Performing Financing (NPF) Islamic banks in Indonesia in 2007-2012. analytical tool used is multiple linear regression using panel data. Results of regression is that the variable Financing to Deposit Ratio (X1) and a significant positive effect on Non Performing Financing, Return on Assets (X2) and a significant negative effect on Non Performing Financing and the inflation rate (X3) and no significant positive effect on Non-Performing Financing.